Investigation of structural, electrical and optical properties of oxygen (O7+) ion irradiated CdZnO thin films for solar cell applications. (September 2019) - A, GuruSampath Kumar; Xuejin, Li; Hong, Xueming; Geng, Youfu; Du, Yu; T, Subba Rao
Abstract: An effective method to improve the properties of nano-structured CdZnO thin films for the application in solar cells is demonstrated. CdZnO thin films have been fabricated on glass substrates by direct current (dc) magnetron sputtering and irradiated with high energetic oxygen ions (O 7+ ) of energy 100 MeV of different SHI fluences of 1E+ 11, 5E+ 12 and 1E+ 13 ions/cm 2, respectively. Structural properties of the films have been investigated by grazing incidence XRD and reveal hexagonal wurtzite structure oriented along c -axis. The crystallinity of the film enhanced gradually at lower ion fluence (1E+11 ions/cm 2 ) thereafter tending towards polycrystalline nature due to the continuous increase in SHI irradiation fluence. The surface roughness (RMS) decreased (from 19 to 11.24 nm) with SHI irradiation fluence which leads to the polycrystalline nature of the films. Optical properties of the films reveal that the band-gap after irradiation decreased due to enhancement in the transmittance. The electrical resistivity of pristine CdZnO films decreased with ion irradiation from 2.47 to 8.55 × 10 –2 Ω-cm. Hall mobility of films increased to 75.4 cm 2 V –1 s –1 with SHI-irradiation fluence from 32 cm 2 V –1 s –1 (pristine) due to a gradual increase in the concentration of charge carriers and grain boundary scattering with the increased mean free path. Highlights: CdZnO thin films deposited by well-known dc-magnetron sputtering technique. Achieved high optical transmittance (89%) and low electrical resistivity (8.55 × 10 −2 Ω-cm). Minimum roughness (11.24 nm) is obtained by ion irradiation with 100 MeV oxygen ions. It is well-suited for the metal contact material for the solar cells.